2015
DOI: 10.1177/1591019915582376
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of vasospasm following aneurysmal SAH using C-arm FDCT parenchymal blood volume measurement in the neuro-interventional suite: Technical feasibility

Abstract: Introduction Cerebral vasospasm is the leading cause of morbidity and mortality in patients with aneurysmal subarachnoid haemorrhage (SAH) surviving the initial ictus. Commonly used techniques for vasospasm assessment are digital subtraction angiography and transcranial Doppler sonography. These techniques can reliably identify only the major vessel spasm and fail to estimate its haemodynamic significance. To overcome these issues and to enable comprehensive non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(29 reference statements)
0
7
1
Order By: Relevance
“…In contrast to FPD-CT studies performed on ischemia 12-15 and on vasospasm 17,18 in our study on bAVMs, perfusion correlated best with CBF. The strongest correlation was found with ASL-CBF.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In contrast to FPD-CT studies performed on ischemia 12-15 and on vasospasm 17,18 in our study on bAVMs, perfusion correlated best with CBF. The strongest correlation was found with ASL-CBF.…”
Section: Discussioncontrasting
confidence: 87%
“…[12][13][14][15] However, recently, it has been shown that in vasospasm, FPD-CT perfusion is both CBV-and CBF-weighted. 17,18 Furthermore, parenchymal blood volume maps obtained from CTA source images 23 have been reported to be either CBV-or CBF-weighted, depending on the order of CTA/ CTP data acquisition. 24 In this study, the glomerular bAVMs showed a perinidal hyperperfusion, with a tendency to normalization with increasing distance from the nidus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we look to expand our diagnostic evaluation with CBV imaging. There have also been few studies on how cerebral vasospasm affects cerebral perfusion . Although these reports demonstrated feasibility of measuring how cerebral vasospasm affects perfusion, there are currently no studies investigating the quantitative change in perfusion after injection of a spasmolytic agent using the FDCT scanner.…”
Section: Introductionmentioning
confidence: 99%